Positioning occupational therapy as a discipline on the research continuum: Results of a cross‐sectional survey of research experience. Issue 4 (30th June 2013) - Pighills, Alison C.; Plummer, David; Harvey, Desley; Pain, Tilley
<x xml:space="preserve">Abstract</x> Background/aim Evidence‐based practice and research are beginning and endpoints on a research continuum. Progression along the continuum builds research capacity. Occupational Therapy has a low evidence base, thus, clinicians are not implementing evidence‐based practice or publishing research. Barriers to implementing evidence‐based practice and engaging in research include a lack of confidence. This research gauged Occupational Therapists' research experience, support needs and barriers, and compared levels of research anxiety between allied health disciplines. Methods A cross‐sectional survey was sent to Health Practitioners in northern Queensland in May–June 2011. Responses about experience, support needs and barriers, between Occupational Therapists, were analysed using Chi‐square 'goodness of fit' tests. Multivariate analysis compared responses between disciplines about research anxiety. This paper reports results for the subset of Occupational Therapists. Results The whole population, consisting of 152 Occupational Therapists, was sent a questionnaire, from which 86 responded. More Occupational Therapists than not had experience of evidence‐based practice and less support was required, but they had little experience of producing research and required more support. The amount of support required for activities along the research continuum was inversely related to the level of experience in these tasks. Barriers included lack of staff and time. Occupational Therapists were more anxious about research (53 of 79, 67%) than all other Health Practitioner disciplines combined (170 of 438, 39%, P < 0.0001). Conclusion A cohesive strategy should focus on consolidating Occupational Therapists' evidence‐based practice skills and building confidence. Clinicians wishing to engage in research need access to academic support. Academics and clinicians should work closely to produce clinically relevant research.